Religiusitas dalam Ruang Publik Agama dan Politik di Era Kontemporer - aqila, hana juhaida (Universitas Islam Negeri Raden Intan Lampung, 2024)
Religiousness, which increasingly influences the public sphere, has become a major focus in contemporary political polemics. This article explores the complex dynamics between religiosity, the public sphere, and political polemics in the current context. Religiosity not only creates individual identities, but also plays a significant role in shaping political narratives and public agendas. However, the emergence of religious extremism and intolerance often triggers tensions in the public sphere, challenging the values of pluralism and tolerance. In the face of these challenges, it is important to understand how religiosity influences political dynamics and how political influences create an environment that affects expressions of religiosity in the public sphere. By examining various perspectives and controversies, this article aims to present a comprehensive picture of the role of religiosity in creating political mindsets and behaviors in this complex contemporary era.